Paulo Fogaça: o artista e seu tempo - CARVALHO, Rosane Andrade de (2008)
Paulo Fogaça: the artist and its time is the result of the study of Paulo Fogaça s artistic work, carried through between years 1969 and 1980, in which we search to understand the bonds of this production with the project of the new national vanguard of years 1960, as for its experimental and engaged character in the social and politic matters of that period. For this, we carry through the presentation of the artistic trajectory of Pablo Fogaça, followed by a general exposition of its workmanships, showing its reference images tied with the agricultural visual universe. Concomitant to this task we make an immersion in the history of the art and the Brazilian culture, of the decades of 1960 and 1970, period of validity of the military government in the country, specifically in the actions, events and artistic proposals that had been absorbed by the desire of renewal of the language and the establishment of a more effective relation between art and Brazilian reality. We choose, thus, a set of Paulo Fogaça s workmanships that point, according to our intentions of analysis, for practical, operative and ideological procedures, at the same time, experimental and compromised with the social political questions that were contemporary to them. This made possible a boarding of the essential aspects that converge and/or diverge with the principles defended and expressed in the project of national vanguard in the middle of 20th century. This route made possible to locate in the production of the artist its critical positioning in the historical panorama deeply lived by him, as well as artistic procedures considered experimental for the time. These aspects insert Paulo Fogaça s workmanship in the set of precursory proposals of the use of new technologies (photograph, super-8 audiovisual and film) in Brazilian artistic language especially in the State of Goias.